2020
DOI: 10.3390/jcm9061686
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Prognosis of Patients with Myocardial Infarction Type 1 and Type 2 with and without Involvement of Coronary Vasospasm

Abstract: While prognoses in relation to myocardial infarction (MI) type have been elucidated in past reports, the results were not consistent, perhaps due to occurrence of Type 2 MI with CVS and its mortality. The Japanese registry of acute Myocardial Infarction diagnosed by Universal Definition (J-MINUET) is a prospective multicenter registry in Japan. In contrast to thromboembolic event-related Type 1 myocardial infarction (MI), clinical features of Type 2 MI, including coronary vasospasm (CVS), are varied due to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 53 publications
(69 reference statements)
1
7
0
1
Order By: Relevance
“…Other studies revealed that the number of men with T2MI was lower than that of women (3,25,26). However, we found that more men than women had T1MI or T2MI, which is very similar to the results of a Japanese study (10). Men in East Asia have a higher rate of MI than men in Western countries.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Other studies revealed that the number of men with T2MI was lower than that of women (3,25,26). However, we found that more men than women had T1MI or T2MI, which is very similar to the results of a Japanese study (10). Men in East Asia have a higher rate of MI than men in Western countries.…”
Section: Discussionsupporting
confidence: 89%
“…Moreover, most study results have indicated that the prognosis of T2MI is not as good as that of T1MI (6)(7)(8)(9). In contrast, a study in the Japanese population found no difference in long-term mortality between T1MI and T2MI, and T2MI accounted for only 5% of the study cases (10). The incidence of T2MI is low in epidemiological studies on this condition; however, these studies have limitations and different diagnostic criteria, judgment processes, detection methods with boundary values, and study populations.…”
Section: Introductionmentioning
confidence: 88%
“…A total of 40 studies were included for analysis13–52 and their characteristics are summarised in online supplemental table S3. They comprised a total of 127 620 participants of whom 98 930 participants (77.5%) were classified as T1MI and 13 803 (10.8%) as T2MI.…”
Section: Resultsmentioning
confidence: 99%
“…The 2007 definition1 was used in 7 (17.5%) studies,15 16 27 29 43 44 52 the 2012 definition2 in 25 (62.5%) studies,13 17 19–21 23–26 30–35 37 39 40 42 45–48 50 51 and the 2018 definition3 in 8 (20%) studies 14 18 22 28 36 38 41 49. Of the 40 studies, 17 (42.5%) were prospective15 16 18 19 22 29 33 34 36 37 43–45 47 48 50 51and 23 (57.5%) were retrospective 13 14 17 20 21 23–28 30–32 35 38–42 46 49 52…”
Section: Resultsmentioning
confidence: 99%
“…Notably, the female sex, a BMI < 25 kg/m 2 , puncture difficulty, the use of a plastic needle, and a 6F sheath were identified as independent predictors of RAS. On a separate note, vasospasm in the coronary artery was found to be useful for predicting the prognosis after Type II MI events [ 12 ].…”
Section: Advances In Pci For Acute Coronary Syndromementioning
confidence: 99%